1989
DOI: 10.1037/0022-0663.81.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Social relations of gifted children as a function of age and school program.

Abstract: This study examined social and personal concomitants of exceptional academic capability in the context of various educational settings. Students in Grades 5, 8, and 10 participated in the study. At each grade level, there were students in classes for the gifted (self-contained gifted), gifted students in regular classes (integrated gifted), and classmates of the integrated gifted (matched and random controls). Subjects completed self-report scales of social competence and feelings about school. Peer nomination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 34 publications
5
32
0
Order By: Relevance
“…Because they are socially vulnerable (Frederickson and Furnham 2004;Gresham and MacMillan 1997;Sale and Carey 1995), students with mild disabilities may be susceptible to being bullied and may compensate by bullying others and by affiliating with peers who support this behavior. On the other hand, academically gifted students tend to be fairly well accepted in late elementary school (Austin and Draper 1981;Schneider et al 1989) and may focus more on academics than social prominence. Therefore, while they tend to be socially prominent and associate with peers who teachers view as being popular, academically gifted students do not appear to be vulnerable to being bullied and seem to be relatively less likely to be involved in bullying.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because they are socially vulnerable (Frederickson and Furnham 2004;Gresham and MacMillan 1997;Sale and Carey 1995), students with mild disabilities may be susceptible to being bullied and may compensate by bullying others and by affiliating with peers who support this behavior. On the other hand, academically gifted students tend to be fairly well accepted in late elementary school (Austin and Draper 1981;Schneider et al 1989) and may focus more on academics than social prominence. Therefore, while they tend to be socially prominent and associate with peers who teachers view as being popular, academically gifted students do not appear to be vulnerable to being bullied and seem to be relatively less likely to be involved in bullying.…”
Section: Discussionmentioning
confidence: 98%
“…Preuss and Dubow (2004) found that academically gifted students were more likely to employ active problem-solving approaches to social stressors, and that being academically gifted moderated the impact of stressors on adjustment. Academically gifted students are rated by teachers as having highly positive levels of social skills (Janke and Lee 1991) and during the elementary school years they are likely to experience high levels of social acceptance and low levels of peer rejection (Austin and Draper 1981;Luftig and Nichols 1990;Schneider et al 1989). Academically gifted students are also more likely to have prosocial or popular friends than their non-gifted peers and less likely to be socially isolated (Farmer and Rodkin 1996;Pearl et al 1998;Schneider and Daniels 1992).…”
Section: Introductionmentioning
confidence: 97%
“…Both Malcolm's and Bradley's profiles illustrate the very real difficulties of some gifted children in finding other children to whom they can relate (Gross, 1993;Robinson & Noble, 1991;Schneider et al, 1989). While high IQ does not necessarily mean adjustment problems (Robinson & Noble, 1991), it can be perceived by others as evidence of maladjustment.…”
Section: Resultsmentioning
confidence: 93%
“…Personal images of school success and acceptance by peers affect achievement. Research on gifted learners shows that their academic self-concepts are higher than those of average learners and their social self-concepts are about the same (Hoge & Renzulli, 1993;Schneider, Clegg, Byrne, Ledingham, & Crombie, 1989). However, some researchers suggest that individual differences may exist in the ways that gifted children perceive their abilities and social relationships (Friedman, 1992;Hoge & Renzulli, 1993).…”
Section: Affective Factorsmentioning
confidence: 93%
See 1 more Smart Citation